Multi-omics analysis of naïve B cells of patients harboring the C104R mutation in TACI - Ramirez, Neftali; Posadas-Cantera, Sara; Langer, Niko; de Oteyza, Andres Caballero Garcia; Proietti, Michele; Keller, Baerbel; Zhao, Fangwen; Gernedl, Victoria; Pecoraro, Matteo; Eibel, Hermann; Warnatz, Klaus; Ballestar, Esteban; et al. (Frontiers in Immunology, 2022)
Common variable immunodeficiency (CVID) is the most prevalent form of symptomatic primary immunodeficiency in humans. The genetic cause of CVID is still unknown in about 70% of cases. Ten percent of CVID patients carry heterozygous mutations in the tumor necrosis factor receptor superfamily member 13B gene (TNFRSF13B), encoding TACI. Mutations in TNFRSF13B alone may not be sufficient for the development of CVID, as 1% of the healthy population carry these mutations. The common hypothesis is that TACI mutations are not fully penetrant and additional factors contribute to the development of CVID. To determine these additional factors, we investigated the perturbations of transcription factor (TF) binding and the transcriptome profiles in unstimulated and CD40L/IL21-stimulated naïve B cells from CVID patients harboring the C104R mutation in TNFRSF13B and compared them to their healthy relatives with the same mutation. In addition, the proteome of stimulated naïve B cells was investigated. For functional validation, intracellular protein concentrations were measured by flow cytometry. Our analysis revealed 8% less accessible chromatin in unstimulated naïve B cells and 25% less accessible chromatin in class-switched memory B cells from affected and unaffected TACI mutation carriers compared to healthy donors. The most enriched TF binding motifs in TACI mutation carriers involved members from the ETS, IRF, and NF-κB TF families. Validation experiments supported dysregulation of the NF-κB and MAPK pathways. In steady state, naïve B cells had increased cell death pathways and reduced cell metabolism pathways, while after stimulation, enhanced immune responses and decreased cell survival were detected. Using a multi-omics approach, our findings provide valuable insights into the impaired biology of naïve B cells from TACI mutation carriers.